EFFET DE LA PARATHYROÏDECTOMIE (PTX) SUR L’EVOLUTION DE LA PRESSION ARTERIELLE CHEZ LES RATS MALES ET FEMELLES DE SOUCHE SPONTANEMENT HYPERTENDUE (SHR) (Sciences & Technologie. C, Biotechnologies, 2011)
The removel of parathyroid glands (PTX) decreases the development of hypertension in young spontaneously hypertensive rats (SHR) and Lyon hypertensive (LH) rats. The purpose of our study was to investigate the effect of parathyroidectomy on chronic evolution of systolic blood pressure (SBP) in young and in aged male and femele SHR rats. Our results indicate that PTX significantly reduces total plasmacalcium (mmol/L) in 6, 10, 22, and 36 weeks old male and femele rats (mean desrease: 30%, p